MEKANISME DEWAN PERWAKILAN RAKYAT DALAM MEMBERIKAN PERTIMBANGAN KEPADA PRESIDEN BERDASARKAN UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - , MUHAMMAD YASIN ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research aims to know the role and mechanism of the House of Representatives in giving consideration to the President in the appointment of Ambassadors and the implications of its considerations for the President. This is normative research that investigate about the principles, norms and synchronization of the regulations that releting to the implementation of the oversight function of the House of Representatives to government, particularly about the appointment of Ambassador by the President. The method that used in this research is library reseach with examine the all primary and second legal literature, and tertiary legal literature that releting with primary problem of this research. The result of research are the House of Representatives has a key position in the oppoinment of Ambassador, based on the 13 article of the 1945 constitution obligate president in orde to be more careful and professional in lifting and receive ambassadors, and this is the right of the Parliament as a representative of all the people of Indonesia to conduct oversight of government. Mechanism of the House in giving consideration to candidates to fill a position on legislation through a plenary session, then the Agency commissioned a plenary meeting of the Council to schedule and assign the discussion to related fittings. There is a political concequence for president if no ettention to parlement consideration. It can discrupt the house and goverment relation, so the policies often conflict with the political attitudes majority in the House.